2018
DOI: 10.1093/nutrit/nuy006
|View full text |Cite
|
Sign up to set email alerts
|

A crucial role for maternal dietary methyl donor intake in epigenetic programming and fetal growth outcomes

Abstract: The fetal origins of health and disease framework has identified extremes in fetal growth and birth weight as factors associated with the lifelong generation of chronic diseases such as obesity, diabetes, cardiovascular disease, and hypertension. Maternal nutrition plays a critical role in fetal and placental development, in part by providing the methyl groups required to establish the fetus's genome structure and function, notably through DNA methylation. The goal of this narrative review is to describe the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 117 publications
3
83
0
10
Order By: Relevance
“…Several studies have previously shown that dietary methionine deficiency led to a direct body mass reduction in fish (Belghit et al, 2014;Gao et al, 2019;Mambrini et al, 1999;Séité et al, 2018), but to our knowledge no data are available on the programming impact of methionine deficiency on body mass. However, several previous findings in mammals demonstrated that maternal methyl-group donor nutrition might affect susceptibility to obesity and metabolic syndrome of offspring in adulthood (McGee et al, 2018). Interestingly, we observed that whatever the first feeding of fry, the 2 week challenge of juveniles with the MD diet increased the HSI, and this effect was even stronger in fish from fry fed the MD diet at the first meal.…”
Section: Bsupporting
confidence: 39%
“…Several studies have previously shown that dietary methionine deficiency led to a direct body mass reduction in fish (Belghit et al, 2014;Gao et al, 2019;Mambrini et al, 1999;Séité et al, 2018), but to our knowledge no data are available on the programming impact of methionine deficiency on body mass. However, several previous findings in mammals demonstrated that maternal methyl-group donor nutrition might affect susceptibility to obesity and metabolic syndrome of offspring in adulthood (McGee et al, 2018). Interestingly, we observed that whatever the first feeding of fry, the 2 week challenge of juveniles with the MD diet increased the HSI, and this effect was even stronger in fish from fry fed the MD diet at the first meal.…”
Section: Bsupporting
confidence: 39%
“…Our study showed that a higher dietary folate intake throughout pregnancy was associated with a higher birth weight Z score and that total folate intake during pregnancy was negatively associated with SGA risks and positively associated with the birth weight Z score. As dietary folate is less stable and has a substantially lower bioavailability than synthetic folic acid (14) , the association of total folate intake during pregnancy with SGA risk in the present study was largely attributed to folic acid supplements. Large-scale cohort studies with more comprehensive information on folate status (dietary folate, folic acid supplements, serum folate, and erythrocyte folate) at multiple time points (before conception, in early pregnancy, in middle pregnancy, and in late pregnancy) are needed to further demonstrate the association of folate intake with intra-uterine growth restriction.…”
Section: Discussionmentioning
confidence: 64%
“…Currently, the underlying molecular mechanisms whereby folic acid can prevent adverse pregnancy outcomes are poorly understood. It is speculated that epigenetic modifications, especially DNA methylation, may be involved in these processes (14) . Folate is an essential component in the one-carbon metabolism pathway as it can provide methyl groups for a series of biochemical reactions, including DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methylation of CpG islands in a gene's promoter region has been associated to a progressive switching off of the gene, and the availability of methyl groups required for methylation depends on a folate-rich diet (e.g., spinach, green leaves, peas, asparagus, etc.) as well as sufficient levels of B12 and B6 vitamins [2,3]. Deficiencies in these micronutrients during early life have been associated with increased risk of cardiovascular, metabolic, and neurological diseases later in life [4,5].…”
Section: Doi: 101159/000490751mentioning
confidence: 99%